Influence of Hydrothermal Parameters on Photocatalytic Activity of BiVO4 for Degradation of Methylene Blue - Truong, Vinh-Tien; Le, Pham-Ngoc-My; Le, Minh-Vien (Universitas Gadjah Mada, 2025)
A facile hydrothermal method has been developed to improve the intrinsic photocatalytic activity of BiVO4. By assessing the effects of three key hydrothermal parameters (temperature, time, and pH levels) on catalytic performance, optimal conditions for maximizing photocatalytic activity were identified. Characterization through XRD, FE-SEM, and UV-DRS demonstrates the crucial role of the (040) facet and reduced non-uniform compressive strain in enhancing the photocatalytic activity of bismuth vanadate. The sample synthesized at 200 °C, pH 1, with 10 h of hydrothermal treatment shows significant decolorization of methylene blue with a comparable rate constant. This study presents a promising approach to synthesizing high-performance photocatalysts through a straightforward synthesis process without the use of directing agents.